Academic self-efficacy, self-regulated learning and academic performance in first-year university students - Alegre, Alberto A. (2014)
The aim of this research was to determine the relationship between academic self-efficacy, self-regulated learning and academic performance of first-year university students in the Metropolitan Lima area. An assessment was made of 284 students (138 male and 146 female students) admitted to a private university of Lima for the 2013-2 term by using a non-probability and incidental procedure and the General Academic Self-Efficacy Questionnaire, the University Academic Self-Regulated Learning Questionnaire; and for the academic performance of every student, their registered weighted GPA was taken into account. Formulated hypothesis was accepted as correlation coefficients resulting from academic selfefficacy; self-regulated learning and academic performance were both positive and significant, but low. In addition, the correlation between academic selfefficacy and self-regulated learning were positive, significant and moderate.